Promoting photocarriers separation in distinctive ternary g-C3N4/Ni2P/ZnO composite with Ni2P electron-bridge - Wei, Wei; Bian, Haiqin; Zhang, XuMing; OuYang, ZhengYu; Zhang, Zhengmei; Wang, Tao (Journal of industrial and engineering chemistry (Seoul, Korea), 2024)
Constructing a Z-type heterojunction is a key factor in reducing interface resistance for accelerating the separationand transfer of photogenerated carriers. Therefore, we built a novel g-C3N4/Ni2P/ZnO composite whichform Z-type heterojunction between g-C3N4 and ZnO employing Ni2P as an electron bridge to decrease theinterfacial resistance leading in fast separation and transfer of photogenerated carriers. The results showed thatthe g-C3N4/Ni2P/ZnO composite has excellent photocatalytic performance with 94.8 % within 80 min for theremoval efficiency of rhodamine B (RhB). The exceptional photocatalytic performance of the g-C3N4/Ni2P/ZnOcan be mainly because the synergistic effects of the Ni2P electron-bridge and Z-type heterojunction which coulddecrease interface resistance between the photocatalysts, accelerate photogenerated carriers separation andtransfer, and then improve the strong redox capacity. In additional, the photogenerated carriers transfer andphotocatalytic mechanisms can be discussed more detail in the paper. This research offers a straightforward andviable approach to synthesizing highly efficient photocatalyst with Z-type heterojunction and transition metalphosphates act as an electron-bridge. KCI Citation Count: 0